(Re)framing Resistance to Culturally Relevant Education as a Multilevel Learning Problem. Issue 1 (March 2019) - Neri, Rebecca Colina; Lozano, Maritza; Gomez, Louis M.
Despite evidence of promise, the adoption of culturally relevant educational (CRE) approaches to teaching and learning remains sporadic and underwhelming. In this chapter, we question this state of affairs by investigating teacher resistance to CRE. Through our examination of the literature, we have come to understand teacher resistance to CRE as a multilevel learning problem that stems from (a) limited understanding and belief in the efficacy of CRE and (b) a lack of know-how needed to execute it. We therefore characterize resistance as a learning problem, rather than a problem of individual compliance, and view contextual variation in its take up as an opportunity to learn. Framing teacher resistance to CRE as a multilevel learning problem provides a way forward by shifting the perception of resistance as simply negative to an understanding of resistance as a diagnostic tool, or warning signal about when, where, for whom, and why a change can be particularly difficult. By representing our review of the literature as a problem space map, we offer a tool that can be used to pinpoint, anticipate, and preemptively address the multilevel factors that contribute to teachers' resistance to CRE.